2005
DOI: 10.1002/jgm.796
|View full text |Cite
|
Sign up to set email alerts
|

Unique features of a pH-sensitive fusogenic peptide that improves the transfection efficiency of cationic liposomes

Abstract: The unique features of GALA to mediate improved transfection efficiencies were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 15 publications
0
53
0
Order By: Relevance
“…These polymers, however, are of limited use due to their cytotoxicity (18). Instead, nontoxic lysogenic peptides, such as Glu-Ala-Leu-Ala (GALA) (19,20) derived from certain viruses or bacteria, are used for endosome escape of micelles and liposomes (21) or are covalently bound to nanoconjugates to deliver water-soluble proteins, antibodies, and nucleic acids (9,22).…”
Section: Inhibition Of Brain Tumor Growth By Intravenous Poly (β-L-mamentioning
confidence: 99%
“…These polymers, however, are of limited use due to their cytotoxicity (18). Instead, nontoxic lysogenic peptides, such as Glu-Ala-Leu-Ala (GALA) (19,20) derived from certain viruses or bacteria, are used for endosome escape of micelles and liposomes (21) or are covalently bound to nanoconjugates to deliver water-soluble proteins, antibodies, and nucleic acids (9,22).…”
Section: Inhibition Of Brain Tumor Growth By Intravenous Poly (β-L-mamentioning
confidence: 99%
“…1,2-Dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE) was purchased from AVANTI Polar Lipids Inc. (Alabaster, AL, USA). Stearyl octaarginine (STR-R8) [6,17] and cholesteryl GALA peptide (Cho-GALA) [15,16] was obtained from Kurabo Industries, Ltd. (Osaka, Japan). Protamine was purchased from CALBIO CHEM (Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…HA is a natural ligand for cancer cells and liver endothelial cells overexpressing CD44, thus it would be expected that HA would be a specific ligand for / targeted to cancer and liver endothelial cells. In that study, we investigated the transgene expression of an R8-MEND modified with HA in liver endothelial cells (liver ECs) (CD44 positive cells), and determined the optimal composition of MEND needed for efficient transgene expression in liver ECs, which possesses an HA-coated lipid envelope modified with the R8 [6,7] and GALA, a pH-sensitive fusogenic peptide for efficient endosomal escape [15,16] (HA-R8/GALA-MEND). 6 The focus of this study was on the mechanism responsible for the cellular uptake pathway and transgene expression of the HA-R8/GALA-MEND.…”
Section: Introductionmentioning
confidence: 99%
“…It can therefore be concluded that the S2 peptide represents a safer targeting moiety than R8 for mitochondrial delivery. comprised of a cellular uptake moiety (R8) and an endosomal escape moiety (GALA) constructed by the multi-layering method (Akita et al, 2009;Akita et al, 2011;El-Sayed et al, 2008;Futaki et al, 2005;Yamada et al, 2012b). A number of nanoparticles were observed to accumulate around the nucleus where most of the mitochondria are located (Fig.…”
Section: Cell Viability and Intracellular Observation Of Df-mito-portermentioning
confidence: 99%